Health literacy needs among unemployed adults: Triangulating interview and scoping review data. (20th October 2021) - Samkange-Zeeb, F; Singh, H; Lakeberg, M; Kolschen, J; Schüz, B; Zeeb, H; Christianson, L; De Santis, K; Brand, T
Abstract: : Disadvantaged populations, including unemployed adults, often exhibit low levels of health literacy. Exploring subjectively perceived health literacy needs in these populations can serve as an entry point for participatory intervention development. We aimed to assess health literacy needs of unemployed adults by triangulating qualitative interviews data and a scoping review. Using a parallel approach, we combined results of an interview study with 10 participants of a job-reintegration program in Germany and a scoping review. The interviews, conducted in early 2021, focused on health topics of interest to the participants and their sources of health-related information. Data were analysed using thematic analysis. For the scoping review, we searched MEDLINE, CINAHL, PsycInfo and SCOPUS up to January 2021 for studies containing "unemployed" AND "health literacy" in titles/abstracts. Study selection and data extraction were done independently by two researchers. Nutrition and physical activity emerged as core themes during the interviews, with some participants referring to the importance of both for mental health. Doctors and the institution running the job-reintegration program were the sources of health-related information often mentioned. The Corona pandemic was reported to have limited physical activity and affected psycho-social well-being. Five out of 2696 studies were included in the review. Four focused on mental health literacy, the fifth assessed information seeking practices in unemployed adults. The qualitative analysis revealed that health literacy needs of unemployed adults go beyond mental health literacy. As nutrition and physical activity impact mental health, interventions targeting such topics might also improve mental health literacy in unemployed adults. Study findings will be discussed with unemployed persons and social workers in co-production workshops that aim to identify and prioritize health literacy needs for intervention development. Key messages: Health literacy programs for unemployed adults should target nutrition and physical activity. Workforce re-integration programs play a pivotal role in improving health literacy of unemployed adults.